(untitled) (Vietnam Journal of Community Medicine, 2023)
Objective: Analyzing the relationship between knowledge and behavior of using packaged milk among high school students in Hanoi. Methods: A cross-sectional descriptive study was conducted on 590 high school students in Hanoi using a questionnaire. The data were analyzed using SPSS 22.0 software. Results: 87.6% of the students knew about milk’s nutritional value for body development, while only 26.6% of the students used milk daily. Research has shown that there is a difference between milk consumption behavior and knowledge. However, this difference is not statistically significant (p=0.259), which shows that there is no clear relationship between knowledge and usage behavior. Conclusion: The knowledge about the impact of milk on students’ health is still low, and the habit of daily milk consumption is not high. There is no significant correlation between knowledge and the use of packaged milk among high school students in Hanoi. Therefore, schools should integrate milk nutrition education for students.